2020
DOI: 10.3233/jad-200586
|View full text |Cite
|
Sign up to set email alerts
|

Role of Executive Functions in the Conversion from Mild Cognitive Impairment to Dementia

Abstract: Background: Recent research pointed to executive dysfunction as a potential early predictor of the progression of mild cognitive impairment (MCI) to dementia in Alzheimer’s clinical syndrome (ACS). Such cognitive impairments account for functional impairments in instrumental activities of daily living (IADL). Objective: The present study analyzes the contributions of executive functions to predict MCI–dementia progression in ACS. Methods: We assessed 145 participants, 51 cognitively unimpaired and 94 MCI. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 51 publications
2
43
0
1
Order By: Relevance
“…Thirteen studies used "CLOX-1" or "Clock Drawing Test (CDT)" [51; 78, 79, 84, 85, 89, 95, 100, 102, 108, 110, 111, 112]; two studies used the "Wisconsin Card Sorting Test -Computer Version (WCST -CV)" [76][77]; ten studies used the "Tower of London (TOL)" [23,28,41,49,68,69,86,87,90,91], six studies used "Zoo Map Test" [24,48,59,93,94,106], two studies used "Tower of Hanoi (TOH)" [31,103]; one study used "Raven's Coloured Progressive Matrices (RCPM)" [21]; one study used "Tower Test (D-KEFS)" [66]; one study used "Groton Maze Learning Test" [83]; one study used "Trail Making Test (B-A)" [109]; one study used "Porteus Maze Test" [109]; one study used "Verbal Fluency Test (fruits and animals version)" [109]; one study used "Action Program Test" [48]; and one study used "Key search Test" [48].…”
Section: Planning (N=37)mentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies used "CLOX-1" or "Clock Drawing Test (CDT)" [51; 78, 79, 84, 85, 89, 95, 100, 102, 108, 110, 111, 112]; two studies used the "Wisconsin Card Sorting Test -Computer Version (WCST -CV)" [76][77]; ten studies used the "Tower of London (TOL)" [23,28,41,49,68,69,86,87,90,91], six studies used "Zoo Map Test" [24,48,59,93,94,106], two studies used "Tower of Hanoi (TOH)" [31,103]; one study used "Raven's Coloured Progressive Matrices (RCPM)" [21]; one study used "Tower Test (D-KEFS)" [66]; one study used "Groton Maze Learning Test" [83]; one study used "Trail Making Test (B-A)" [109]; one study used "Porteus Maze Test" [109]; one study used "Verbal Fluency Test (fruits and animals version)" [109]; one study used "Action Program Test" [48]; and one study used "Key search Test" [48].…”
Section: Planning (N=37)mentioning
confidence: 99%
“…One study [48] performed three tests to assess planning ability and observed a worse performance in MCI in only two of them (Action Program Test and Zoo Map Test). The remaining twenty-one studies reported poor performance in MCI than healthy subjects [28,31,41,49,59,66,68,69,76,77,83,84,85,89,92,93,94,95,108,109].…”
Section: Planning (N=37)mentioning
confidence: 99%
See 2 more Smart Citations
“…Even within the a-MCI classification, some people convert to AD in a short time while other patients remain stable for longer intervals, and providing patients and their carers with informative prognosis is extremely challenging. Previous studies based on different types of biomarkers have identified some genetic [4,5], cognitive [6,7], environmental [8][9][10][11][12], and neuroimaging predictors [13][14][15][16] of conversion to dementia. Degeneration in the cholinergic system, whose neurons are located in the basal forebrain and project to the hippocampus and frontal and cingulate cortices, is associated with memory dysfunctions and behavioural symptoms in patients with AD [17][18][19].…”
Section: Introductionmentioning
confidence: 99%